The willingness of Generation Z to financially support CSR: A central European study - Radka MacGregor Pelikánová; Robert K. MacGregor (DANUBE: Law, Economics and Social Issues Review, 2020)
Sustainability, with its three pillars, is projected into Corporate Social Responsibility (CSR) and their effectiveness and efficiency depend upon the operation of the multi-stakeholder model. Both the EU and the EU member states depone clearly that, via CSR, we can exit from the COVID-19 crises stronger and better. The feasibility of the CSR depends upon the eager support of all stakeholders, including consumers. Therefore, it is highly relevant to assess whether the new group of consumers, known as Generation Z, is open to financially support CSR, to what extent and why and/or under what conditions. These three research questions became the foundation of a survey of 179 college students paying for their tertiary study at a private university in Prague. The survey included both closed and open question, brought forth a highly revealing and surprisingly consistent message about the conditional and rather generous readiness of this new generation of consumers in Central Europe, and led to a set of recommendations.
Keywords: 330; Corporate Social Responsibility; Financial Readiness; Generation Z